EVALUASI PERTUMBUHAN TANAMAN UJI KETURUNAN JATI (Tect ona gra ndis L.f.) MENGGUNAKAN ANALISIS MULTIKRITERIA - Hery Kurniawan (Widyariset, 2010)
This research was aimed to determine the rank of tree family in the teak (Tectona grandis L.f.) progeny test based on multi criteria analyses. Research was conducted using deductive approach by collecting data on experiment site consisting of 10 blocks. The proposed criteria and indicators were based on literature study focusing on (1) simple measurement in the field, (2) principle of management objective, and (3) basic principle of silviculture. The selected criteria were stem quality, crown condition and tree growth, and each criteria was derived into indicators and verifiers. Based on the frequency of appearance in the top 25% on each block, the top ten superior families were seedlot number 90 with 8 times, followed by seedlot number 11 and 31 with 7 times, and then seedlot number 10, 106, 124, 15, 18, 4, and 46 with 6 times, respectively.